Динаміка показників мікроциркуляції при комплексному лікуванні інфікованих і гнійних ран у дітей - Спахі, Олег Володимирович; Пахольчук, Олексій Петрович; Spakhi, O. V.; Pakholchuk, A. P. (My University, 2016)
Microcirculation system is one of the main factors ensuring the metabolic homeostasis in tissues. Purpose of the study the dynamics of indicators of microcirculation in children with infected wounds and festering wounds when exposed to an alternating magnetic field and liposomal_antibacterial solution. Materials and methods. We observed 212 children infected and purulent wounds. Patients of the main group with purulent wounds on the wound exposed to an alternating magnetic field and liposomal antibiotic solution, and with infected wounds during surgical treatment of the wound freshly injected liposomal-bacterial solution. To study the dynamics of blood flow to the wound area using the method of laser Doppler flowmetry. Results and its discussion. At day 1 mean parameter microcirculation at the wound site is significantly increased in comparison with the contralateral region myogenic oscillation amplitude increased, and compared with those in the control area. On the 3rd day of treatment in patients of the main group of indicators of microcirculation in the wound area decreased by 68,2 ± 2,5% in, and myogenic amplitude vibrations in the wound — by 76,4 ± 3,4%, the amplitude of the oscillations decreased neurogenic wound area to 78,3 ± 3,6%. On day 7, patients of the main group of the average parameter of microcirculation in the wound area decreased by 47,6 ± 2,4% as compared to the 3-mi for days. Conclusions. 1. Laser Doppler flowmetry is a sensitive method for the study of capillary blood flow in the wound area, which allows its application early diagnosis of wound healing stages. 2. Determination of microcirculation at the wound site can be used as criteria for evaluation of the wound process flow for the control treatment efficacy. 3 Treatment of infected and purulent wounds using an alternating magnetic field with liposomal-antibacterial solution improves microcirculation and create conditions for the manifestation of the greater efficiency of drugs and other mechanisms of action.
Dynamics of indicators of microcirculation in the complex treatment of purulent wounds and infected children
Keywords: інфіковані рани; гнійні рани; флоуметрія; мікроциркуляція; діти; infected wounds; festering wounds; flowmetry; microcirculation; children